Perceptions, facilitators and barriers of physical activity among people living with HIV: a qualitative study - Brenda Kitilya; Erica Sanga; George PrayGod; Bazil Baltazar Kavishe; Kia Ditlevsen; Robert Peck; Mette Frahm Olsen (BMC, 2023)
Abstract Background People living with HIV (PLWH) have low levels of physical activity. Using the social ecological model to understand perceptions, facilitators and barriers of physical activity in this population is of importance for developing contextualised interventions to improve physical activity in PLWH. Method This was a qualitative sub-study conducted between august and November 2019 as part of a cohort study on diabetes and associated complications in HIV infected in Mwanza, Tanzania. Sixteen in-depth interviews and three focus groups with nine participants in each were conducted. The interviews and focus groups were audio recorded, transcribed and translated into English. The social ecological model was considered during the coding and interpretation of the results. Transcripts were discussed, coded and analyzed using deductive content analysis. Results Forty-three PLWH aged 23-61 years participated in this study. The findings showed that most PLWH perceived physical activity as beneficial to their health. However, their perceptions of physical activity were rooted within existing gender stereotypes and roles in the community. Running and playing football were perceived as activities for men while household chores activities were for women. Further, men were perceived to do more physical activity than women. For women, household chores and income-generating activities were perceived as sufficient physical activity. Social support and engagement of family members and friends in physical activity were reported as facilitators of physical activity. Reported barriers of physical activity were lack of time, money, availability of physical activity facilities and social support groups, and poor information on physical activity from health care providers in HIV clinics. Human-immunodeficiency virus (HIV) HIV infection was not perceived by PLWH as a barrier for doing physical activity but most family members did not support them to do physical activity, fearing that it might worsen their condition. Conclusion The findings demonstrated differing perceptions, facilitators and barriers of physical activity among PLWH. Interventions addressing awareness, gender stereotypes and roles related to physical activity from individual to community level are needed. Supportive environment and infrastructures are needed to improve physical activity levels in PLWH in Tanzania.